The Existence of Sanggar Genessa in Caring for Kolintang Traditional Music - Ambar Sulistyowati (Universitas Negeri Medan, 2023)
Nowadays, the development of kolintang music is experiencing a phase of saturation, which can be said to be running in place. The marginalization of traditional kolintang musical instruments due to the increasing existence of modern music. In addition, the lack of interest in traditional musical instruments such as kolintang, including the marginalization of traditional musical instruments by modern musical instruments and the inability of traditional musical instruments to gain a place in the hearts of the younger generation. The presence of Sanggar Genessa in the Kawanua Harmony in the Jayapura Regency area seeks to find the best way to preserve traditional kolintang music in the midst of the mainstream of modern music development. Another vision is to introduce traditional kolintang music to the wider community. This research aims to find out the existence of Sanggar Genessa in Jayapura Regency, Papua in preserving traditional kolintang music. This research uses a qualitative approach. The research found that Sanggar Ganessa was established to be a forum for arts and cultural activities, especially reviving traditional kolintang music outside the Minahasa area. The concern and love of the Kawanua Family Harmony who are members of Sanggar Ganesa for kolintang traditional music can be seen from the efforts to transform this music along with developments in the modern era. This musical transformation is based on the life of the Kawanua Family Harmony which is full of love, solidarity and shared responsibility to preserve Minahasa's cultural heritage. This local art treasure has been passed down from generation to generation and is maintained not only as a form of entertainment, but also as a form of mutual care.